Memahami Kekerasan Terhadap Kelompok Minoritas dalam Konteks Kerukunan Beragama - syafaah, nayla; Saumantri, Theguh (CV Kalimasada Group, 2024)
This article discusses violence against minority groups in the context of religious harmony in Indonesia. The main focus of this research is to understand the factors that lead to violence and its impact on interfaith harmony. This study uses a qualitative approach with a literature review method, where data is collected through text analysis and written data from various available sources. The research findings indicate that violence against minority groups is often triggered by intolerance, lack of interfaith understanding, and structural discrimination. Additionally, economic and political factors significantly exacerbate the situation. The study finds that achieving better harmony requires joint efforts from the government, society, and religious leaders to enhance interfaith dialogue, strengthen minority protection regulations, and educate the public on the importance of tolerance. These findings are expected to contribute to the development of more inclusive policies and effective strategies to address violence against minority groups. Keywords: violence, minority groups, religious harmony, intolerance, interfaith dialogue